2008
DOI: 10.1016/j.bandc.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual–attentional and motor-intentional bias in near and far space

Abstract: Spatial bias demonstrated in tasks such as line-bisection may stem from perceptual-attentional (PA) "where" and motor-intentional (MI) "aiming" influences. We tested normal participants' line bisection performance in the presence of an asymmetric visual distracter with a video apparatus designed to dissociate PA from MI bias. An experimenter stood as a distractor to the left or right of a video monitor positioned in either near or far space, where participants viewed lines and a laser point they directed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 29 publications
5
68
3
Order By: Relevance
“…A reaction time advantage has also been observed in extrapersonal space and upper VF conditions (Previc & Blume, 1993). Previous research has typically shown a stronger leftward bias in peripersonal space than in extrapersonal space (Bjoertomt et al, 2002;Garza et al, 2008). Consistent with the relation between viewing distance and the upper and lower VFs, we observed a stronger leftward bias in the lower VF on a task completed in peripersonal space.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A reaction time advantage has also been observed in extrapersonal space and upper VF conditions (Previc & Blume, 1993). Previous research has typically shown a stronger leftward bias in peripersonal space than in extrapersonal space (Bjoertomt et al, 2002;Garza et al, 2008). Consistent with the relation between viewing distance and the upper and lower VFs, we observed a stronger leftward bias in the lower VF on a task completed in peripersonal space.…”
Section: Discussionsupporting
confidence: 88%
“…This is a significant finding as there had been a lack of work studying upper and lower VF differences in perceptual asymmetries and the greyscales task had not previously been used to study them. VF differences were not associated with viewing distance, and although some work had shown a space-based dissociation (Bjoertomt et al, 2002;Garza et al, 2008;Longo & Lourenco, 2006;Varnava et al, 2002), others failed to identify any differences (Longo & Lourenco, 2006, Wilkinson & Halligan, 2003. We concluded that although VF differences were not linked with space-based processing differences, the proposed relation between space-based and VF processing does not have strong empirical support either.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, the percentage of units related to the kinematic parameters was very low in all regions (in every region: <2%). To verify that the decreased neuronal modulations are not because of reduced attention to the passive observation task (Khan, Heinen, & McPeek, 2010;Garza, Eslinger, & Barrett, 2008;Chiba, Yamaguchi, & Eto, 2005;Boussaoud, 2001), we repeated the analysis using data limited to only the first 5 min of every session, during which higher attention of the subject was observed. This analysis found very low percentages of cells related to the kinematic parameters …”
Section: Discussionmentioning
confidence: 99%
“…Brief peripheral cues are known to draw the perceived middle of the line towards their location (Bultitude and Aimola Davies 2006;Nicholls and Roberts 2002). Attention is also drawn to the side of the line with more 'mass' (McCourt and Garlinghouse 2000) or towards an experimenter standing to one side of the display (Garza, Eslinger, and Barrett 2008).…”
Section: Methodsmentioning
confidence: 99%